DISPERSAL TRENDS OF THE INVASIVE SPECIES ALPINE PENNY-CRESS (NOCCAEA CAERULESCENS, BRASSICACEAE) IN KARELIA, NW RUSSIA - Кравченко, Алексей Васильевич; Бахмет, Ольга Николаевна; Тарасенко, Виктор Владимирович; Тимофеева, Вера Владимировна; Kravchenko, Alexey; Bakhmet, Olga; Tarasenko, Viktor; Timofeeva, Vera (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2020)
An invasive species, Alpine penny-cress (Noccaea caerulescens (J. Presl & C. Presl) F. K. Mey.) was for the first time encountered in the Republic of Karelia in the Town of Sortavala in 1909. Over the past 110 years, the species has become quite frequent in the northern Ladoga area, with a fairly rapid dispersal across the area observed before WWII. Further advance of the species to the north and east of this territory has obviously slowed down, although occasional findings have been reported from the very north of the republic (Pyaozersky settlement) and east of Lake Onego (Lobsky settlement). Such a pattern of the species’ current distribution in Karelia can be attributed to the geochemical characteristics of the northern Ladoga area. This territory is rich in heavy metal deposits and ore occurrences, has numerous and extensive outcrops of the crystalline basement, and, as a result, its soils feature elevated background concentrations of heavy metals. Being a metallophyte, N. caerulescens found itself in a favorable environment here. Nevertheless, there is reason to expect further spread of the species across the region.